Chlamydomonas IFT70/CrDYF-1 Is a Core Component of IFT Particle Complex B and Is Required for Flagellar Assembly - Fan, Zhen-Chuan (The American Society for Cell Biology, 2010)
DYF-1 is a highly conserved protein essential for ciliogenesis in several model organisms. In Caenorhabditis elegans, DYF-1 serves as an essential activator for an anterograde motor OSM-3 of intraflagellar transport (IFT), the ciliogenesis-required motility that mediates the transport of flagellar precursors and removal of turnover products. In zebrafish and Tetrahymena DYF-1 influences the cilia tubulin posttranslational modification and may have more ubiquitous function in ciliogenesis than OSM-3. Here we address how DYF-1 biochemically interacts with the IFT machinery by using the model organism Chlamydomonas reinhardtii, in which the anterograde IFT does not depend on OSM-3. Our results show that this protein is a stoichiometric component of the IFT particle complex B and interacts directly with complex B subunit IFT46. In concurrence with the established IFT protein nomenclature, DYF-1 is also named IFT70 after the apparent size of the protein. IFT70/CrDYF-1 is essential for the function of IFT in building the flagellum because the flagella of IFT70/CrDYF-1–depleted cells were greatly shortened. Together, these results demonstrate that IFT70/CrDYF-1 is a canonical subunit of IFT particle complex B and strongly support the hypothesis that the IFT machinery has species- and tissue-specific variations with functional ramifications.